Au nanoparticle modified single-crystalline p-type LaRhO3/SrTiO3 heterostructure for high performing VOCs sensor. Issue 14 (1st October 2020) - Meng, Zhi; Tong, Bin; Shen, Lei; Xu, Liqiang; Chu, Weiwei; Wei, Wensen; Xu, Xueli; Liu, Yonglai; Pi, Li; Zhang, Shile; Zhou, Chun; Ma, Zongwei; et al.
Abstract: Since the discovery of two-dimensional electron gas (2DEG) confined at perovskite LaAlO3 /SrTiO3 (LAO/STO) interface, extensive efforts have been devoted to explore novel high-performance all oxide electronic devices, including gas sensors. Among perovskite oxides, LaRhO3 (LRO) possesses unique p-type conductivity and catalytic properties, which offer promising benefits for sensing volatile organic compounds (VOCs) molecules. In this work, single-crystalline p-type LRO thin film was epitaxially grown on STO (110) substrate as a high-quality sensing channel. Drastic improvement of sensing performance of LRO probed by 50 ppm ethanol was accomplished by appropriate Au decoration layer, e.g., an increased response (from 2.5 to 8.4), reduced optimal operation temperature (from 325 to 275 °C), decrease of response/recovery time (from 100/85 to 54/23 s) and improvement of detection limit (from 5000 to 250 ppb). X-ray photoelectron spectroscopy (XPS) indicates that Au nanoparticles facilitates the formation of reactive chemisorbed oxygen species, which substantially trigger the charge exchange occurring at ethanol/LRO interface. Our work highlights the importance of surface engineering toward high-performance perovskite based VOCs sensors.